A 6-month longitudinal and comparative study of corneal biomechanical properties after SMILE with two different optical zone sizes - Yizhuo Gong; Xinmeng Wang; Mingkun Yu; Peipei Zu (PLoS ONE, 2025)
Purpose To precisely evaluate the independent influence of two different optical zone (OZ) sizes (6.3 mm vs. 6.5 mm) on corneal biomechanical properties within 6 months after Small Incision Lenticule Extraction (SMILE) using multivariable-adjusted statistical models. Methods This retrospective study included myopic patients who underwent SMILE between 2022 and 2024. Patients were grouped into two groups based on the planned OZ: Group A (6.3 mm, 44 eyes) and Group B (6.5 mm, 54 eyes). Corneal biomechanical parameters were measured using the Corvis ST preoperatively and at 1, 3, and 6 months postoperatively. Linear Mixed Models (LMM) were used to assess the independent effect of OZ size, adjusting for key baseline covariates and accounting for inter-eye correlation by including a random intercept for patient identifier (ID). Results A total of 98 eyes were analyzed. Baseline analysis revealed a significant imbalance between the groups, with Group A (6.3 mm OZ) having higher myopia and a greater corneal stromal ablation depth (both P < 0.001). The central finding from the LMM analysis was that, after adjusting for all covariates, optical zone size (6.3 mm vs. 6.5 mm) had no independent, statistically significant effect on 11 of the 12 biomechanical parameters (all P > 0.05), with the sole exception of Ambrosio Relational Thickness Horizontal (ARTH) (P = 0.012). In contrast, several preoperative covariates, particularly corneal stromal ablation depth and preoperative central corneal thickness, were identified as significant predictors of multiple postoperative biomechanical parameters. Conclusion The independent effect of a 0.2 mm difference in optical zone size on corneal biomechanical properties after SMILE appears to be limited. After comprehensive statistical adjustment, the results suggest that preoperative anatomical and surgical parameters, especially corneal stromal ablation depth, are the primary drivers of the postoperative biomechanical response, rather than the minor difference in OZ size itself. This study underscores the importance of confounder adjustment in refractive surgery research and suggests that maximizing the residual stromal bed may be more critical for maintaining corneal biomechanical integrity than fine-tuning the optical zone diameter.